INTEGRATED MODEL FOR SUPPLIER SELECTION AND PERFORMANCE EVALUATION - de Araújo, Maria Creuza Borges; Alencar, Luciana Hazin (The South African Journal of Industrial Engineering, 2015)
This paper puts forward a model for selecting suppliers and evaluating the performance of those already working with a company. A simulation was conducted in a food industry. This sector has high significance in the economy of Brazil. The model enables the phases of selecting and evaluating suppliers to be integrated. This is important so that a company can have partnerships with suppliers who are able to meet their needs. Additionally, a group method is used to enable managers who will be affected by this decision to take part in the selection stage. Finally, the classes resulting from the performance evaluation are shown to support the contractor in choosing the most appropriate relationship with its suppliers.